Public Support for Green, Inclusive, and Resilient Growth Conditionality in International Monetary Fund Bailouts. - Heinzel, Mirko; Kern, Andreas; Metinsoy, Saliha; Reinsberg, Bernhard (International Studies Quarterly, 2025)
The International Monetary Fund (IMF) has recently expanded its policy scope to include a broader set of policies to promote green, inclusive, and resilient growth. How does this expansion affect the support for the IMF and its loans among the populations of borrowing countries? We conducted a pre-registered survey experiment with 2,694 respondents from three borrower countries—Argentina, Kenya, and Pakistan. We show that support for IMF programs increases by approximately 24 percent compared to traditional programs when the IMF includes good governance, anti-poverty, climate change, and gender equality measures in its programs. Our results imply that people do not uniformly reject the imposition of policies of global governance institutions but have well-defined preferences over policy measures. Our findings contribute to debates on the backlash against international institutions by highlighting that citizens are willing to accept sovereignty intrusion when they push for policy goals aligned with their policy preferences.